Sustainable value added as we do not know it - Straková, Juliana (Business: Theory and Practice, 2015)
Entrepreneurial activities play an important role in a mixed economy. Incorporating the nowadays call for sustainable practices, enterprises cope with the evaluation of their efforts in the economic area as well as in the environmental area on their own. The method called Sustainable Value Added might very well solve this problem. It is based on the idea that enterprises actually create value when using environmental resources. However, opposite to the original idea, we do not think that environmental resources create the same value, never mind what resource we take. In this article, we propose the improvement of the original Sustainable Value Added arguing that the best for distinguishing various value creations is to weight the environmental resources according to their impact on environment. Based on an integrated analysis of the financial as well as environmental reports of selected German enterprises, we can conclude that when weighting environmental resources, enterprises performed worse than when simple averaged. However, the weighing reduces the risk of considering all resources to have the same impact on environment and on Sustainable Value Added results, as well.